Cuidado ao idoso frágil na atenção primária à saúde: programa mais vida - Lirica Salluz Mattos Pereira (2017)
The interactions of biological, psychological and social factors throughout life, culminate in a state of greater vulnerability that may compromise the autonomy and independence of the elderly, which has been associated to the emergence of functional disability, dependence on daily living activities and more recently, to fragility. The general objective of this study was to analyze how care for the frail elderly person occurs by the professionals of the Family Health Strategy teams and the Family Health Support Unit of Primary Health Care from the implementation of the care plan elaborated by the multiprofessional team of the Centro Mais Vida. It is a descriptive, exploratory, cross-sectional study developed using the quanti-qualitative approach. The study scenario defined was the Centro Mais Vida and Basic Health Units of the Central-South, Northeast and Venda Nova sanitary districts of the city of Belo Horizonte. The research subjects were 34 graduated health professionals from the Family Health Team (FHT) and the Family Health Support Center (FHSC). Data collection was performed in two stages, being the first part composed by documentary analysis of 362 care plans to identify the profile and clinical functional classification of the elderly served in the Mais Vida Program. The second stage of the data collection was performed through an individual interview with the professionals of the Family Health Team (FHT) and Family Health Support Center (FHSC). The data were collected through a semi-structured interview and analyzed by the Thematic Content Analysis technique, with theoretical methodological orientation of E. Morins Complexity Theory. In all the stages of the study, Resolution Nº. 466/2012 of the National Health Council was considered. It was identified in the analysis of care plans that of the 187 fragile elderly, 70,44% were female and 51,3% studied on average one to four years. In the evaluation of activities of daily living, only 8% were totally independent and 6,4% completely dependent. It was identified that 26% had previous diagnosis of Type 2 Diabetes Mellitus and 73% of Systemic Arterial Hypertension and 9% of Chronic Renal Disease. Insomnia was cited by 28% of the elderly and 37% had depression. It was identified that 71% of the elderly were eutrophic, 16% with some degree of obesity and 5% with hyporexia or unintentional weight loss and malnutrition. Urge urinary incontinence was cited by 17% of the elderly and 65% presented some degree of postural instability. It is noteworthy that 62% of the elderly presented some cognitive alteration and 51% were referred to the reference geriatrics. In the qualitative analysis emerged the following categories and subcategories: Care for the fragile elderly in Primary Health Care and the subcategories: the fragmentation of the fragile elderly care and the care for the frail elderly: challenges and the perspectives for integral care; in addition to the following categories: Programa Mais Vida: tool for the fragile elderly care line in Health Care Networks; Care Plan: the course, strategies and challenges for the implementation process; Permanent education in the area of geriatrics and gerontology and clinical supervision as support in the care of the frail elderly; Care for the frail elderly: challenges and perspectives for the integrality of care. It is concluded that there is a reductionism in health actions, guided by the biomedical hegemonic model, resulting in the fragmentation of care and a health care model focused on the acute and disease-oriented, and there are no specific strategies for this life cycle. In this context, the Programa Mais Vida is considered by some professionals as a tool for the fragile elderly care line in the Health Care Networks, but there is an incipient knowledge and lack of clarity of the professionals in relation to the Program. In the implementation of the care plan, there are adaptations, according to the reality experienced by each elderly person, as well as considerations regarding the interventions indicated in the plan, since the professionals evaluate and define the conduct according to the health history of the elderly and its socioeconomic context. Among the obstacles that had an impact on the implementation process, are the lack of articulation, communication and integration of PHC and CMV professionals, the lack of information on the return of the elderly, the logistics of delivering the results of exams and access to the care plans, as well as lack of family support. There is mention that self-care is compromised in cases of illiteracy and cognitive incapacity. There is also evidence of the lack of training and permanent education in geriatrics and gerontology, which impacts the care offered. It is suggested the construction of a care line for the elderly's health, creation of groups and leisure spaces guided by aging, creation of support strategies through systematic home visits and actions directed at the caregiver, institution of parenting meetings between the teams and the implementation of training programs and permanent education.